Analysis of the problems of humanization of education in Ukraine - Sazhko, G.; Shekhovtsova, V. (My University, 2013)
In recent years it has become particularly clear that the education system of Ukraine did not justify the hopes the training of specialists internationally competitive labor market, and the ability to restructure public life reorganization of production, preservation of culture and national culture, the environment, law and order. Scientific research in the field of philosophy, social psychology, pedagogy, ascertain the reduced quality of human phenomenon, reducing his moral stability, capacity for survival, creativity, cultural arrangement of his own life. The way forward is seen as one - this humanistic orientation of education, the revival of spirituality and moral perfection.
Keywords: the crisis in education; the problem of humanization; the system of training the individual; concept of education; humanization